Discussion with Professor Dr. Jack - Yeo Jiin Yih, Jacinta (UiTM Sarawak, 2018)
On 28 may 2018 representatives from UiTM Sarawak led by the Rector, Professor Dato Dr. Jamil Hamali, discussed with professor Dr. Jack, the Chief Scientist of Sarawak on introducing many smart, digital campus initiatives